2017
DOI: 10.1039/c7ra04566b
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of graphene/activated carbon/polypyrrole flexible supercapacitor electrodes

Abstract: A ternary composite of graphene/activated carbon/polypyrrole (GN/AC/PPy) used as an electrode active material for supercapacitors has been synthesized via vacuum filtration and anodic constant current deposition methods. The ACs sandwiched between GN sheets can be used as flexible substrates for PPy nanoparticles, and the microscopic morphologies and electrochemical performances of GN/AC/PPy electrodes were synthesized and designed through regulating different deposition current densities and deposition times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 45 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…Based on this value, the PPy loading per unit area of the KF@PPy/ f -CNT11 freestanding electrode was estimated to be 3.6 mg cm −2 . The PPy loading achieved for our electrode is much higher than those achieved for many previously reported PPy-based freestanding electrodes [8,25,51,52,53,54,55,56,57,58,64,65,66,67]. The mass fraction of KF was low, approximately 16 wt %, in the freestanding electrode.…”
Section: Resultsmentioning
confidence: 60%
“…Based on this value, the PPy loading per unit area of the KF@PPy/ f -CNT11 freestanding electrode was estimated to be 3.6 mg cm −2 . The PPy loading achieved for our electrode is much higher than those achieved for many previously reported PPy-based freestanding electrodes [8,25,51,52,53,54,55,56,57,58,64,65,66,67]. The mass fraction of KF was low, approximately 16 wt %, in the freestanding electrode.…”
Section: Resultsmentioning
confidence: 60%
“…Graphene can also be incorporated with CPs and other carbon materials such as CNT, activated carbon, 65 carbon dots, 66 and carbon fiber. Zhou et al 67 found that the length of the CNT gives significant effect on the supercapacitive performance of the GO/PEDOT/CNT ternary composite.…”
Section: Graphene/other Carbon Material/ Conducting Polymermentioning
confidence: 99%
“…2 Graphene has attracted considerable attention of researchers due to its good thermal stability, conductivity, impermeability, high specic surface area, and barrier properties against oxygen, water and corrosive ions. 3,4 Owing to those excellent properties, graphene were studied in some applications such as graphene composite supercapacitor electrodes, 5 thermoelectric materials, 6,7 and solvent removal functional materials 8 etc. However, due to strong van der Waals forces between layers, graphene is so easy to aggregate that has challenged to disperse and limit the scope of further applications.…”
Section: Introductionmentioning
confidence: 99%